Heterogeneity among orf virus isolates from goats in Fujian Province, Southern China. - Xuelin Chi (PLoS ONE, 2013)
Orf virus is a parapoxvirus that causes recurring contagious ecthyma or orf disease in goat, sheep and other wild and domestic ruminants. Infected animals show signs of pustular lesions on the mouth and muzzle and develop scabs over the lesions. Although the infection is usually cleared within 1-2 months, delayed growth and associated secondary infections could still impact the herds. Orf virus can also infect humans, causing lesions similar to the animals in pathological histology. Prior infection of orf virus apparently offers little protective immunity against future infections. Several gene products of orf virus have been identified as responsible for immunomodulatory functions. In our recent study of orf virus isolates from an area along the Minjiang River in northern Fujian Province, we found a high heterogeneity among isolates from 10 farms within a 120-kilometer distance. Only two isolates from locations within 1 km to each other had same viral genes. There is no correlation between the geographical distance between the corresponding collection sites and the phylogenetic distance in ORFV011 or ORV059 genes for any two isolates. This finding suggests that there are diverse populations of orf virus present in the environment. This may in part contribute to the phenomenon of recurring outbreaks and heighten the need for better surveillance.